1999
DOI: 10.1097/00007632-199909010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Attachments of the Posterior Layer of Lumbar Fascia

Abstract: Both superficial and deep laminae of the posterior layer are more extensive superiorly than previously thought. This may have implications for certain tests used in assessment and management of low back pain such as the slump and "nonorganic" tests. The thickness of the superior attachments is variable. Their capacity for load bearing is yet to be quantified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
25

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 35 publications
2
60
0
25
Order By: Relevance
“…Cadaveric dissections of the lumbar region clearly identify a well-developed compartment of posterior spinal muscles encased by the posterior and middle layer of the lumbodorsal fascia [2,13]. The posterior layer divides the intrinsic (paraspinal) from the extrinsic (upper limb and serratus posterior) muscles of the back.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cadaveric dissections of the lumbar region clearly identify a well-developed compartment of posterior spinal muscles encased by the posterior and middle layer of the lumbodorsal fascia [2,13]. The posterior layer divides the intrinsic (paraspinal) from the extrinsic (upper limb and serratus posterior) muscles of the back.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior layer divides the intrinsic (paraspinal) from the extrinsic (upper limb and serratus posterior) muscles of the back. The posterior layer is composed of two clearly distinct superficial and deep layers that encompass the iliocostalis, longissimus, and multifidus muscles [2,13,14]. Fascial continuity of the posterior layer exists with the latissimus dorsi superiorly with that of the superficial layer with the fascia in the dorsal spine, and inferiorly with its extensive attachments to the gluteus medius and maximus and the sacrum and ilium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recommend that researchers develop more comprehensive reference standards for PNP to accurately assess the concurrent validity of ULNTs and continue investigating the predictive validity of ULNTs for prognosis or treatment response. J Orthop Sports Phys Ther 2012;42 (5) ity when it changes with movement of a distant body part that further loads or unloads the nervous system (eg, contralateral neck sidebending increases a sensory response in the forearm). 12,38 Moving a distant body part to evaluate a ULNT response is referred to as structural differentiation.…”
Section: T T Synopsismentioning
confidence: 99%
“…The alignment of the collagen fibres reveals the direction of the load bearing function and is the basis for the effective load transfer from spine to pelvis, legs and arms [1,23]. It has been shown that tensional stiffness of the different layers of the TLF influences spinal stability, such as in resisting spinal flexion or extension [2,3].…”
Section: Structural Function Of the Tlfmentioning
confidence: 99%